Elastomeric Polymers for Retrofitting of Reinforced Concrete Structures against the Explosive Effects of Blast. (23rd September 2012) - Raman, S. N.; Ngo, T.; Mendis, P.; Pham, T.
Abstract : The main distinction of blast load from other types of dynamic loadings is its impulsive nature, where the loads usually act for a very short duration but transmit very high impulsive pressures. This paper presents an overview of the present retrofitting techniques in use to enhance the capacity of structural elements to withstand the effects of blast loads, and introduces an alternative retrofitting approach by utilizing polymer coatings. The authors have demonstrated the positive effects of this approach by conducting a numerical investigation on the behavior of an unretrofitted reinforced concrete panel subjected to the blast load from a 2 kg charge at 1.6 m stand-off distance, and subsequently comparing its performance with several polymer coated panels. The analysis was performed by using an explicit nonlinear finite element (FE) code. The results demonstrate the contributions of this technique in terms of panel displacement control and energy dissipation. Considering that the polymer coating can also act as a protective layer in improving the durability of structural materials, this technique can also be optimized favorably to enhance the overall sustainability of structures.